PENENTUAN DAYA TAMPUNG BEBAN CEMARAN INDIKATOR PENCEMAR BOD (BIOLOGICAL OXYGEN DEMAND) DENGAN SOFTWARE QUAL2E (Studi Kasus : Sungai Tuntang, Jawa Tengah) - Ivan Ilianta Ginting (Jurnal Teknik Lingkungan, 2012)
Tuntang river is part of the watershed Tuntang, with the main river length ± 111.39 km. the amount of pollution of Tuntang river capacity need to know at any time to determine the condition of the river Tuntang used for various activities. Therefore, it is necessary to identify indicators of load capacity of pollutant contamination Biological Oxygen Demand (BOD) using QUAL2E software. The simulation results at minimum flow (dry season) compared to the standard quality PP No. 82 Tahun 2001 found that Tuntang River can fullfill the quality standard BOD contaminant load class III (with a capacity of 41.73 to 772.03 kg / day) at km 14 km -18, and 85-106 km and meets the standard contaminant load class IV (with a capacity of 59.62 to 2560.521 kg / day) at 8-46 km and 81-109 km. Simulation results on maximum discharge (wet season) compared to the standard quality PP No. 82 Tahun 2001 found that Tuntang River meets the quality standard BOD contaminant load class III (with a capacity of 142.97 to 2907.51 kg / day) at km 8 - 44 and km 81-106 and can fullfill the quality standard contaminant load class IV (with a capacity of 440.84 to 10055.89 kg / day) at KM1-107.